2017
DOI: 10.3389/fpsyt.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Association of Certain Neuropsychiatric Disorders Following Vaccination of Children and Adolescents: A Pilot Case–Control Study

Abstract: BackgroundAlthough the association of the measles, mumps, and rubella vaccine with autism spectrum disorder has been convincingly disproven, the onset of certain brain-related autoimmune and inflammatory disorders has been found to be temporally associated with the antecedent administration of various vaccines. This study examines whether antecedent vaccinations are associated with increased incidence of obsessive–compulsive disorder (OCD), anorexia nervosa (AN), anxiety disorder, chronic tic disorder, attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…Under incomplete mitochondrial development and hypoxic conditions of placenta, organogenesis and angiogenesis of embryo‐fetus require proper architectural organization and functioning of trophoblast epithelium for providing and consuming appropriate and sufficient growth factors/hormones, nutrients, enzymes, trace elements (metals) and respective constituent or induced receptor molecules. Exposure of the embryo‐fetus to flu shot and incipient, could pose serious threats to survival and health of both mother and fetus including altered nutrients in organogenesis, transition of myoblasts to myotube development, ratios of constituent/induced receptors, as potential contributors in growth retardation or growth promotion, fetus abortion or impaired health of newborn, infant, toddler, that also influence immunity during adulthood and aging process 1,5,8,20,24,27‐85,87‐125,129,192 (manuscript in preparation)] (Figures 1, 3 and 4).…”
Section: Vaccine Toxicities: Retardation Of Mitochondria and Immune Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Under incomplete mitochondrial development and hypoxic conditions of placenta, organogenesis and angiogenesis of embryo‐fetus require proper architectural organization and functioning of trophoblast epithelium for providing and consuming appropriate and sufficient growth factors/hormones, nutrients, enzymes, trace elements (metals) and respective constituent or induced receptor molecules. Exposure of the embryo‐fetus to flu shot and incipient, could pose serious threats to survival and health of both mother and fetus including altered nutrients in organogenesis, transition of myoblasts to myotube development, ratios of constituent/induced receptors, as potential contributors in growth retardation or growth promotion, fetus abortion or impaired health of newborn, infant, toddler, that also influence immunity during adulthood and aging process 1,5,8,20,24,27‐85,87‐125,129,192 (manuscript in preparation)] (Figures 1, 3 and 4).…”
Section: Vaccine Toxicities: Retardation Of Mitochondria and Immune Rmentioning
confidence: 99%
“…As shown below, pathogen‐specific vaccines (eg, polio, swine flu, hepatitis a, b, c, MMRs, meningitis, shingles, anthrax, pertussis, HPV, SARS, Ebola, Zika, or ‘covid‐19’) and incipient weaken/destroy the complex electrobiology of immunity and Not Promote It ! 1,5,8,11,17,20,27–178 …”
Section: Author's Summary Of Accidental Discoveries‐multistep Immune Dysfunction: Setting Stage For Vaccine‐induced Injuriesmentioning
confidence: 99%
“…Those with newly diagnosed AN were more likely than matched controls to have had any vaccination in the previous 3 months (hazard ratio (HR): 1.80; 95% CI: 1.21–2.68), and those with AN, OCD, and anxiety disorder were more likely than controls to have received influenza vaccinations during the previous 3, 6, and 12 months. HRs >1.40 were also found for hepatitis A vaccination with OCD and AN, for hepatitis B with AN, and meningitis with AN and chronic tic disorder [ 54 ]. Other research has found that the therapeutic use of 13-cis-RA (isotretinoin) is associated with the onset of depression, psychosis, and suicide [ 55 ], and both depression and cognitive disturbances in 1% to 11% of patients with acne [ 56 ].…”
Section: Unifying Hypothesis On the Pathogenesis Of Vaccine Injurymentioning
confidence: 99%
“…The authors concluded that the low absolute risk and high public health benefit favored continued adherence to recommended vaccination schedules. 25 As in the PANDAS claims-data studies, there is no distinction between, or knowledge of, a severe dramatic onset vs a gradual onset. The magnitudes of the hazard ratios-the strength of the association, were usually close to 1.…”
Section: Epidemiologic Studies-pansmentioning
confidence: 99%